2017
DOI: 10.1002/2016jf004036
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Bingham Canyon rock avalanches (Utah, USA) resolved from topographic, seismic, and infrasound data

Abstract: The 2013 Bingham Canyon Mine rock avalanches represent one of the largest cumulative landslide events in recorded U.S. history and provide a unique opportunity to test remote analysis techniques for landslide characterization. Here we combine aerial photogrammetry surveying, topographic reconstruction, numerical runout modeling, and analysis of broadband seismic and infrasound data to extract salient details of the dynamics and evolution of the multiphase landslide event. Our results reveal a cumulative intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Seismic broadband observations of such events allow us to invert for the 3-D landslide force history and time-dependent center of mass position and -in combination with topography data -enable seismologists to fully describe a mass wasting event from remote (hundreds to thousands of kilometers of distance) observations. Such observations have revealed scaling laws that link seismic observables to the mass and momentum of massive landslides (Ekström and Stark, 2013), help to constrain numerical models of landslides (Moretti et al, 2012(Moretti et al, , 2015, and support observations of frictional weakening during sliding events (Lucas et al, 2014;Levy et al, 2015;Delannay et al, 2017).…”
Section: Introductionmentioning
confidence: 55%
“…Seismic broadband observations of such events allow us to invert for the 3-D landslide force history and time-dependent center of mass position and -in combination with topography data -enable seismologists to fully describe a mass wasting event from remote (hundreds to thousands of kilometers of distance) observations. Such observations have revealed scaling laws that link seismic observables to the mass and momentum of massive landslides (Ekström and Stark, 2013), help to constrain numerical models of landslides (Moretti et al, 2012(Moretti et al, , 2015, and support observations of frictional weakening during sliding events (Lucas et al, 2014;Levy et al, 2015;Delannay et al, 2017).…”
Section: Introductionmentioning
confidence: 55%
“…Alternatively, the smaller event(s) could trigger the larger event if the stress perturbation is sufficiently destabilizing. Smaller collapses that decay in number over time can follow a large event, akin to earthquake aftershocks (e.g., Allstadt et al, 2017;Moore et al, 2017), which may reflect the adjustment of the slope to the new stress configuration.…”
Section: Recurrence and Time Clusteringmentioning
confidence: 99%
“…While the single-force approximation can still be useful, these factors complicate the interpretation (Allstadt, 2013b;Moretti et al, 2015;Coe et al, 2016). Singleforce inversions can be used to roughly estimate mass and trajectory for simple landslides (Ekström and Stark, 2013;Yamada et al, 2013;Hibert et al, 2014a;Schöpa et al, 2018), to understand the sequence of events (e.g., Allstadt, 2013b;Iverson et al, 2015;Moore et al, 2017), to extract quantitative information such as velocity and basal friction (Brodsky et al, 2003;Moretti et al, 2012;Yamada et al, 2013), and to constrain numerical landslide models (Favreau et al, 2010;Moretti et al, 2015;.…”
Section: Source Theorymentioning
confidence: 99%
“…The rockslide may displace a few meters or tens of meters (Glueer et al, 2019), disintegrate over a number of hours (Schneider et al, 1993), or transition into a catastrophic, flow-like rock avalanche (Coe et al, 2016). If catastrophic failure occurs, a rockslide may initially slide for a significant distance, translating and rotating over 3D topography, before fragmenting and becoming flow-like (Davies et al, 1999;De Blasio, 2011;Bowman et al, 2012;Aaron and Hungr, 2016b;Moore et al, 2017). have shown that the bulk basal shear strength that acts on the rupture surface of rock avalanches soon after failure appears to be dependent on the volume of the rock avalanche.…”
Section: Introductionmentioning
confidence: 99%